PUBLIC RELATIONS COMMUNICATION STRATEGY OF UINSU ON THE INSTAGRAM PLATFORM TO ENHANCE A POSITIVE IMAGE AMONG NEW STUDENTS - Fitria, Putri Kiara; Sumanti, Solihah Titin (Journal Analytica Islamica, 2025)
This study aims to analyze the communication strategy implemented by the Public Relations of the State Islamic University of North Sumatra (UINSU) through the Instagram platform in order to form a positive image among new students. The data was analyzed using the Theory Image in the corporate image category. The problems studied in this study are how the strategy is built by UINSU Public Relations and what are the inhibiting and supporting factors for the implementation of UINSU's Public Relations strategy. The research method used is a qualitative-descriptive approach with data collection techniques in the form of observation, interviews, and documentation of the Instagram account @uinsu_official and new students in the 2024/2025 academic year. The results of the study are expected to be able to reveal the strategy and effectiveness of the content published by the official account @uinsu_official as well as the supporting and inhibiting factors for the implementation of public relations communication strategies. This study also provides theoretical contributions to the development of communication science as well as practical recommendations for institutions in improving the reputation and involvement of new students through social media.